Regional Differences in the Frequency of BRCA1 and BRCA2 Variants in Northeastern Japan: A Cohort Study - Hidekazu Shirota; Akimitsu Miyake; Maako Kawamura; Shuhei Suzuki; Kensuke Saito; Jun Yasuda; Hiroyuki Shibata; Motonobu Saito; Takeshi Iwaya; Hiroshi Tada; Muneaki Shimada; Naoki Kawamorita; et al. (Cancer Medicine)
ABSTRACT Background Germline mutations in BRCA1/2 are known to cause hereditary tumors in the breast, ovary, and other organs. With the widespread adoption of comprehensive diagnostics, including comprehensive genomic profiling (CGP) tests for solid tumors, many patients with BRCA1/2 variants have been identified. Methods In this study, we extracted and analyzed cases of BRCA1/2 variants that were presumed to be germline, which were repeatedly detected using the CGP test for solid tumors in northeastern Japan. The frequencies of BRCA1/2 variants in regional areas were compared with those of healthy individuals or nationwide cancer cohorts to investigate regional distribution. Results Our findings revealed regional disparities in BRCA1/2 pathogenic germline variants, while variants of unknown significance (VUS) showed no such differences. The regional distribution of BRCA1 and BRCA2 variants showed distinct patterns: pathogenic variants of BRCA1 exhibited regional differences and were less prevalent compared to VUS, whereas BRCA2 variants, including both pathogenic variants and VUS, did not exhibit such clear regional localization. This discrepancy in regional distribution between BRCA1 and BRCA2 variants could be attributed to factors such as the diversity of the genome, gender differences, and cancer types. Conclusions These results highlight the importance of considering regional differences in comparative cohort studies, particularly in assessing the differential extension of mutations in pathogenic changes and VUS. Moreover, a presumption of pathogenicity variants would need to be discussed at the regional level.